Organoselenium-Catalyzed Aza-Wacker Reactions: Efficient Access to Isoquinolinium Imides and an Isoquinoline N-Oxide - Li, Huimin; Liao, Lihao; Zhao, Xiaodan (Synlett, 2019)
An efficient approach for the organoselenium-catalyzed aza-Wacker reaction of olefinic hydrazones and an oxime to form isoquinolinium imides and an isoquinoline N-oxide is developed. This transformation involves a direct intramolecular C–H amination using hydrazones and an oxime as imine-type nitrogen sources. This work not only provides a new approach for the construction of isoquinoline derivatives, but also expands the scope of nitrogen sources in electrophilic selenium catalysis.
Keywords: organoselenium catalysis; aza-Wacker reaction; C–H amination; hydrazones; isoquinoline derivatives